Maternal collapse in tertiary care center over a year - Basanti, Namoijam; Devi, Khumanthem Pratima; Tauro, Sheral Raina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Maternal collapse is defined as an acute event involving the cardiorespiratory systems and/or central nervous system resulting in a reduced or absent conscious level (and potentially cardiac arrest and death). Causes can be hypovolemia, hypoxia, electrolytes imbalance, thromboembolism, toxicity, etc. Since the maternal physiology is different from the general adult, modifications are necessary during the cardiorespiratory resuscitation process. This study aimed to find out the prevalence and causes of maternal collapse. Methods: It was a hospital based cross-sectional study conducted in the department of obstetrics and gynecology, RIMS for a duration of one year. Results: The total number of maternal collapse during the study period was 43, with a mortality of 8 among them. Uterine rupture and placenta accreta spectrum were the topmost causes for maternal collapse. Conclusions: The study of the factors involved in maternal collapse will help in better understanding of the causes and management of the same.